2018
DOI: 10.1186/s12917-018-1658-y
|View full text |Cite
|
Sign up to set email alerts
|

A laparoscopic approach for removal of ovarian remnant tissue in 32 dogs

Abstract: BackgroundSurgical treatment of ovarian remnant syndrome (ORS) in dogs usually necessitates large celiotomies and considerable manipulation of organs because of the relatively deep position of ovarian remnant tissue, large patient size, and often encountered adhesions. In women, laparoscopic treatment of ORS is successful and has significant advantages over laparotomy. Since laparoscopic ovariectomy has significant advantages over open ovariectomy in dogs, including reduced surgical stress and postoperative pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
0
14
0
5
Order By: Relevance
“…Sex steroids are known mainly for their role in fertility and reproduction, but during stressful events, they are also mediated by the HPA when it recognizes a nociceptive stimulus [32,33]. The effects of gonadocorticoids vary, but, in general, testosterone, LH, and FSH concentrations decrease during the first 5 post-operative days [32,34,35].…”
Section: Related Gonadotropic Hormones: Fsh Lh and Testosteronementioning
confidence: 99%
“…Sex steroids are known mainly for their role in fertility and reproduction, but during stressful events, they are also mediated by the HPA when it recognizes a nociceptive stimulus [32,33]. The effects of gonadocorticoids vary, but, in general, testosterone, LH, and FSH concentrations decrease during the first 5 post-operative days [32,34,35].…”
Section: Related Gonadotropic Hormones: Fsh Lh and Testosteronementioning
confidence: 99%
“…Classification of studies by organ system is presented in Tables S1 and S2. Numbers of studies and participants were reported within each organ/system group including female genital tract (22 studies [n = 1407 dogs]), 1,7,11,20,30‐47 urinary tract (7 studies [n = 114]), 3,48‐53 stomach (9 studies [n = 250]), 10,18,54‐59 intestinal tract (5 studies [n = 48]), 60‐64 liver (5 studies [n = 288]), 12,17,65‐67 adrenal gland (5 studies [n = 62]), 13,28,68‐70 spleen (7 studies [n = 111]), 19,71‐76 and other (4 studies that included gastropexy and ovariectomy procedures [n = 148]) 9,77‐79 . One experimental study, in which colopexy in seven male dogs was described, was classified as intestinal tract even though these dogs were also sterilized during the surgical procedure because this study reported only complications and outcomes related to colopexy 63 .…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of minimally invasive laparoscopic surgery compared with conventional open surgery are numerous and include increased diagnostic accuracy, improved visibility, 1 decreased patient stress and postoperative pain, faster patient recovery, reduced infection rate, and decreased morbidity and hospitalization stay 2‐8 . The use of laparoscopic and laparoscopic‐assisted techniques is becoming increasingly commonplace in small animal surgery, most notably for elective procedures including ovariectomy and elective gastropexy 9‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, Sontas explained that the causes of ORS may include the presence of ovarian residue resulting from a surgical technical error or the presence of accessory ovarian tissues at the adjacent tissue (Sontas et al, 2007). These remnant tissues will continue to secrete sex hormones and the bitches will then present clinical signs of proestrus, estrus, ovarian or mammary tumors, or stump pyometra (Ball et al, 2010;van Nimwegen et al, 2018). The symptoms mentioned above may occur within a week to several years following the neutering of the animal (van Nimwegen et al, 2018;Vissiennon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These remnant tissues will continue to secrete sex hormones and the bitches will then present clinical signs of proestrus, estrus, ovarian or mammary tumors, or stump pyometra (Ball et al, 2010;van Nimwegen et al, 2018). The symptoms mentioned above may occur within a week to several years following the neutering of the animal (van Nimwegen et al, 2018;Vissiennon et al, 2010). Furthermore, these remnant tissues will continue to function as normal ovary and may be risk of developing ovarian tumor (Oliveira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%